Cytosolic access of Mycobacterium tuberculosis: critical impact of phagosomal acidification control and demonstration of occurrence in vivo. - Roxane Simeone; Fadel Sayes; Okryul Song; Matthias I Gröschel; Priscille Brodin; Roland Brosch; Laleh Majlessi (PLoS Pathogens, 2015)
Mycobacterium tuberculosis (Mtb) uses efficient strategies to evade the eradication by professional phagocytes, involving--as recently confirmed--escape from phagosomal confinement. While Mtb determinants, such as the ESX-1 type VII secretion system, that contribute to this phenomenon are known, the host cell factors governing this important biological process are yet unexplored. Using a newly developed flow-cytometric approach for Mtb, we show that macrophages expressing the phagosomal bivalent cation transporter Nramp-1, are much less susceptible to phagosomal rupture. Together with results from the use of the phagosome acidification inhibitor bafilomycin, we demonstrate that restriction of phagosomal acidification is a prerequisite for mycobacterial phagosomal rupture and cytosolic contact. Using different in vivo approaches including an enrichment and screen for tracking rare infected phagocytes carrying the CD45.1 hematopoietic allelic marker, we here provide first and unique evidence of M. tuberculosis-mediated phagosomal rupture in mouse spleen and lungs and in numerous phagocyte types. Our results, linking the ability of restriction of phagosome acidification to cytosolic access, provide an important conceptual advance for our knowledge on host processes targeted by Mtb evasion strategies.